The Relationship Between Mother’s Safety Competency and The Risk Perception in Sharenting Activities - Birgitta Bestari Puspita; Paulus A Edvra (Fakultas Ilmu Komunikasi UKWMS, 2022)
Social media has attracted many groups of society to use it for various goals. Some parents use it as digital gallery for their children’s photographs, which is now becomes common digital activity in Instagram. In the midst of Instagram popularity, there is risk, lurks children’s safety. The risk includes misuse of children’s images or even kidnapping threat. The activity of sharing online information about children by parents is known as ‘sharenting’, which is mostly practiced by mothers. By practicing ‘sharenting’, they might violate children’s privacy rights. To avoid this, parents' digital literacy skill is needed. Parents’ digital literacy may affect their skill in using digital media, including safety competency. Thus, this research aims to measure the relationship between mother’s safety competencies and risk perception of children’s privacy in ‘sharenting’ activities. The method for this research is web survey, using questionnaire to collect the data from 385 mothers who have children under 13 years old, in accordance with Instagram’s age restriction policy, who live in East Java. The results show that the safety competency factor only correlates 14.4% with the mothers' risk perceptions of children's privacy. Another factor of 85.6% is not seen in this study. The weak relation between mothers’ safety competency and their risk perception of child’s privacy in this research shows that there are many other factors that can be explored in the future research.ABSTRAK Media sosial menarik banyak kalangan masyarakat untuk menggunakannya dengan berbagai tujuan. Beberapa orang tua menggunakannya sebagai galeri digital untuk foto anak-anak mereka, yang sekarang menjadi aktivitas digital yang umum di Instagram. Di tengah popularitas Instagram, terdapat risiko yang mengintai keselamatan anak-anak. Risiko tersebut termasuk penyalahgunaan gambar anak-anak atau bahkan ancaman penculikan. Kegiatan berbagi informasi daring tentang anak oleh orang tua dikenal dengan istilah ‘sharenting’, yang paling banyak dilakukan oleh para ibu. Dengan mempraktikkan 'sharenting', mereka mungkin melanggar hak privasi anak-anak. Untuk menghindari hal tersebut, orang tua perlu memiliki keterampilan literasi digital. Literasi digital orang tua dapat memengaruhi keterampilan mereka dalam menggunakan media digital, termasuk kompetensi keamanan. Penelitian ini bertujuan untuk mengukur hubungan antara kompetensi keamanan ibu dan persepsi risiko atas privasi anak dalam kegiatan 'sharnting'. Metode penelitian yang digunakan adalah survei web, dengan menggunakan kuesioner untuk mengumpulkan data dari 385 ibu yang memiliki anak di bawah 13 tahun, sesuai dengan kebijakan pembatasan usia Instagram, yang tinggal di Jawa Timur. Hasil penelitian menunjukkan bahwa faktor kompetensi keamanan hanya berkorelasi 14,4% dengan persepsi risiko ibu terhadap privasi anak. Faktor lain sebesar 85,6% tidak terlihat dalam penelitian ini. Lemahnya hubungan antara kompetensi keselamatan ibu dan persepsi risiko mereka terhadap privasi anak dalam penelitian ini menunjukkan bahwa masih banyak faktor lain yang dapat dieksplorasi dalam penelitian selanjutnya.